Sistem Peramalan Indeks Harga Konsumen (IHK) Menggunakan Metode Double Exponential smoothing (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2018)
The Consumer Price Index (CPI) is an index number that measures the average price of goods and services consumed by households. CPI is often used to measure the inflation rate of a country and also as a consideration for the adjustment of salaries, wages, pensions, and other contracts. The purpose of this research is to provide a future picture to the government in providing a policy that will come. The data used in this final project is the Consumer Price Index (CPI) in Indonesia from January 2010 to December 2016. From the CPI data from January 2010 to December 2016, a continuous improvement process in the latest forecasting object emphasizing on the decline of Priority exponential on the older object experiences. From the data plot, including the type of data trend, the more suitable method is using double exponential smoothing. To do the forecasting test is done by calculating the percentage error and the mean absolute percentage error. After going through the process of forecasting using double exponential smoothing method, the result of forecasting Consumer Price Index (CPI) in Indonesia in January 2017 is 127.24 at alpha 0.9 with MAPE(Mean Absolute Percentage Error) 1.24. The smallest MAPE between alpha will be used as a forecast.